(untitled) (International Journal of Engineering Sciences & Management Research, 2017)
Food safety, free from pesticides/ chemicals, healthy environmental concern etc., are the reasons for buying organic food products. But even though many of the consumers are not buying the organic foods. The objective of this paper is to find the awareness towards organic foods from non – users. This study is conducted in vellore region from 75 respondents. The data for the research is collected from primary source through the questionnaire. The data is analysed with the help of statistical tool like percentage analysis, chi-square analysis, correlation and anova method.The interpretations are summarized and suggestions are provided for the organic food products on the analysis.